Implementation of a simple real-time algorithm for ventricular fibrillation detection in a microcontroller - Dell'aquila, Carlos Rubén (2015)
This paper describes the implementation of an algorithm for detecting episodes of Ventricular Fibrillation (VF) in a MSP430F6659 microcontroller. Statistical and digital signal processing techniques were used in its design. The valid-ity of its performance was carried out in 3 ECG records from the MIT-BIH Arrhythmia Database, 1 record of the MIT-BIH Malignant Ventricular Arrhythmia Database and in 10 rec-ords of the Creighton University Ventricular Tachyarrhyth-mia Database. These records correspond to patients who suf-fered of VF episodes during the ECG study. The algorithm was able to detect 100% of VF events and has a time of computa-tion of approximately 100 μs.